Comparative Study of Construction/Flat Patterns and Grading Patterns Application in Clothing Making: A Case Study on Womens Clothing Practices - Marniati, Marniati (International Journal for Educational and Vocational Studies, 2020)
This study aimed to measure the implementation of the practice in the womens clothing course in terms of the skill variable making construction/flat clothing patterns, applying the grading pattern and making womens clothing. This study used a quantitative approach. The research subjects were all students who programmed the womens clothing course. 43 students of the UNESA Fashion Design Education undergraduate study program. Data analysis used 2x4 factorial ANOVA followed by a comparison of the mean using SPSS software. The honest real difference test (Tukey test) was used to test the difference between the two data at the 5% significance level. Observations were made on two things, namely the length of time for making patterns and clothes, on industrial and custom-made clothing. Industrial clothing consists of one-pieces, blouses/tunics, skirts, and pants, while costume-made clothing consists of deuce pieces, long dresses, short dresses, and modern kebaya. The method of making patterns reads into two ways, namely flat and grading. The results showed that the grading method can speed up the time for making industrial and custom-made clothing patterns. The manufacture of one-piece industry clothing takes longer than others. Meanwhile, the long costume-made dress takes longer than the others